1788 comprising A narrative of the expedition to Botany Bay and A complete account of the settlement at Port Jackson - Tench, Watkin 1759?-1833 (Text Publishing Company, 1996)
Watkin Tench stepped ashore at Botany Bay with the First Fleet in January 1788. He was in his late twenties, a captain of the marines, and on the advanture of his life. Insatiably curious, with a natural genius for storytelling, Tench wrote two enthralling accounts of the infant colony - A Narrative of the Expedition to Botany Bay and A Complete Account of the Settlement at port Jackson. Tench brings to life the legendary figures of Bennelong, Arabanoo and Governor Phillip, and records the voices of convicts trying to make new lives in their new country